Следы древних миграций в генофонде крымских и казанских татар: анализ полиморфизма Y-хромосомы - Агджоян, А.Т.; Утевская, О.М.; Схаляхо, Р.А.; Дибирова, Х.Д.; Почешхова, Э.А.; Юсупов, Ю.М.; Мансуров, Р.И.; Наумова, Е.А.; Атраментова, Л.А.; Балановская, Е.В.; Балановский, О.П. (Фактори експериментальної еволюції організмів, 2013)
Aims. The comparative analysis of gene pools of the Crimean and Kazan Tatars by the Y chromosome markers. Methods. The molecular, statistical and cartographical methods were used. Results. A high heterogeneity and lack of a dominant haplogroup were found for the gene pool of Crimean Tatars. Conclusions. The Crimean Tatars gene pool includes the «Middle Eastern», «Mediterranean» and, to a lesser extent, «Asian» haplogroups, and for Kazan Tatars the «Finno-Ugric» haplogroups are typical. The gene pools of the Crimean and Kazan Tatars are placed on the different «poles» of the genetic space of Eurasian Turkic peoples.